2020
DOI: 10.1002/jsfa.10335
|View full text |Cite
|
Sign up to set email alerts
|

Use of mineral multi‐elemental analysis to authenticate geographical origin of different cultivars of tea in Guizhou, China

Abstract: BACKGROUND The geographical origin of tea (Camellia sinensis) can be traced using mineral elements in its leaves as fingerprints. However, the role that could be played by soil mineral elements in the geographical authentication of tea leaves has been unclear. In this study, 22 mineral elements in 73 pairs of tea leaves and soils from three regions (Pu'an, Duyun, and Liping) in Guizhou, China, were determined using inductively coupled plasma mass spectrometry (ICP‐MS) and inductively coupled plasma atomic emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…For example, Ma et al [ 12 ] studied the geographical production origin of several green teas from China by employing linear discriminant analysis based on the composition of 37 metal elements—including rare earth elements—quantified by inductively coupled plasma-mass spectrometry (ICP-MS). The determination of specific stable isotopes and elemental composition has also been described to assess the authenticity of teas [ 13 , 14 , 15 , 16 , 17 , 18 ]. Volatile profiling carried out by gas chromatography (GC) was also reported for the authentication of commercial powdered tea extracts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ma et al [ 12 ] studied the geographical production origin of several green teas from China by employing linear discriminant analysis based on the composition of 37 metal elements—including rare earth elements—quantified by inductively coupled plasma-mass spectrometry (ICP-MS). The determination of specific stable isotopes and elemental composition has also been described to assess the authenticity of teas [ 13 , 14 , 15 , 16 , 17 , 18 ]. Volatile profiling carried out by gas chromatography (GC) was also reported for the authentication of commercial powdered tea extracts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [13] found that sweet potato noodles made from small granule fractions were of higher quality than noodles made from large granule fractions. Zhang et al [14] studied the particle diameter of starch granules at the base, middle, and top of sweet potato tubers, which can be used to different types of food processing. Sahlström et al [15] showed that weight and form ratio (height/width) of bread were promoted by small Agranules (size about 12 mm).…”
Section: Introductionmentioning
confidence: 99%
“…In 1689, Ovington records that tea was taken by the Banias in Surat without sugar, or mixed with a small number of conserved lemons, and that tea with some spices added was used against headache, gravel, and gripe. The tea leaves for such use may have come from China (Zhang et al 2020). While experimenting to introduce tea in India, British colonists noticed that tea plants with thicker leaves also grew in Assam, and these, when planted in India, responded very well (Karlsson 2022).…”
Section: A Brief History Of Teamentioning
confidence: 99%